Respuestas
Respuesta dada por:
7
si debido a que:
![\frac{5}{8} + \frac{3}{8} = \frac{8}{8} = 1 \frac{5}{8} + \frac{3}{8} = \frac{8}{8} = 1](https://tex.z-dn.net/?f=+%5Cfrac%7B5%7D%7B8%7D++%2B++%5Cfrac%7B3%7D%7B8%7D++%3D++%5Cfrac%7B8%7D%7B8%7D++%3D+1)
Espero haberte ayudado
SALUDOS!!!!!!!;)
Espero haberte ayudado
SALUDOS!!!!!!!;)
hiphop1525p6xujc:
muchas gracias
Respuesta dada por:
0
Respuesta:
:D
Explicación paso a paso:
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años